POTENSI PENGELOLAAN HUTAN RAKYAT DI DESA SIBEDI SULAWESI TENGAH - Abdul Rahman; Golar Golar; Syukur Umar; Sudirman Dg. Massiri; Anwar Anwar; Hendra Pribadi; Moh Syam Guslim (Universitas Tadulako, 2022)
The potential for community forest management with forests has been going on for a long time, because land management with forestry plants provides benefits for people's lives. The limited knowledge and education of the Sibedi villagers caused some villagers to encroach on the forest. This study aims to determine the potential of community forests, community interaction in managing forest resources in Sibedi Village, Marawola District, Sigi Regency. This study uses a survey method to identify communities that community forests management. The data analyzed are descriptive and qualitative. The results show is potential for and community interaction with forest resources in Sibedi Village. The level of dependence on community forests in Sibedi Village, some people understand the importance of the existence of forest resources. The community understands that the existence of forest resources can open up opportunities for them to be managed in order to meet their family's needs and the economy as a result of managing forest resources.